Документальні прийоми оперативного контролю в сільськогосподарських підприємствах - Мельник, Катерина Петрівна; Melnyk, K. P. (Луцький національний технічний університет, 2015)
Проведено детальне дослідження практики оперативного контролю щодо необхідності та потреби застосуванні при його здійсненні документальних прийомів. Підкреслено важливість оперативної контрольної інформації в процесі прийняття управлінських рішень по коригуванню негативних явищ в процесі виробництва сільськогосподарської продукції. Спираючись на склад і характеристику об’єктів оперативного контролю, а також на необхідність постійного нагляду (спостереження) за операціями і процесами з ними, розкрито економічний зміст контрольної інформації, що пропонується відображати у запропонованих формах внутрішніх оперативних звітах. Розроблені форми є одночасно інформаційним джерелом для прийняття оперативних управлінських рішень по виправленню відхилень виробничого процесу та основою для ефективного застосування документальних прийомів оперативного контролю. A detailed study of the practice on the need for operational control and application requirements when implementing its documentary techniques. Emphasized the importance of operational control information in decision-making on adjustment of negative phenomena in the production of agricultural products. Based on a detailed analysis of the information needs of managers different levels of advanced economies field and also taking into account scientific findings revealed that not all business operations, processes and phenomena are objects of operational control. Therefore singled out and described a list of objects that primarily require supervision and constant monitoring management. Based on the structure and characteristics of objects of operational control, and the need for constant supervision (supervision) for transactions and processes them, reveals the economic content of the control of the information display is offered in the proposed form of internal operational reports. The form is both a source of information for making operational management decisions to correct deviations production process and the basis for the effective use of documentary techniques operational control. Detailed methods of use classical documentary techniques, taking into account the characteristics and role in enhancing operational control effectiv management. The proposed concrete ways of improving the methodology and information support of operational control in agricultural enterprises. It is proposed to use a combination of techniques factual and documentary control provides for the use of operational control subjects actual data are recorded and presented in the media, which are formed on-line: just (on request) or at the end of the working day (shift). Combining techniques of documentary and actual control contributes to: 1) save time because they do not require constant presence controller controlled process of transformation of the object; 2) coordination of units in case of need for urgent examination of the actual control object; 3) a comparison of individual subjects of control and fair assessment of the quality and reliability of the control information.
Methods documented operational control of agricultural enterprises
Keywords: оперативний контроль; оперативне управління; інформація; об’єкт контролю; документальні прийоми; внутрішня звітність; управлінське рішення; operational control; operational management; information; object control; documentary techniques; internal reporting; management decision